Impulse Buying in E-Commerce Livestreaming: A Dual-Process Examination of Flash Sales and Gender Differences - Andika; Della Nanda Luthfiana; Nadia; Tiara Nur Anisah (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2026)
Objective: This study examines how scarcity cues embedded in flash sales in e-commerce livestreaming environments influence impulse buying behavior. Drawing on the Stimulus–Organism–Response (SOR) framework and the Technology Acceptance Model (TAM), the study distinguishes between quantity-based and time-based scarcity and explores how these cues shape consumers' cognitive and emotional responses. The model proposes a sequential process in which perceived usefulness and positive emotions strengthen the urge to buy impulsively, thereby leading to impulse buying behavior. Gender is also examined as a moderator of the structural relationships in the model. Design/Methods/Approach: Data were collected via an online cross-sectional survey of 308 consumers with prior experience purchasing through livestreaming commerce platforms. The model was tested using partial least squares structural equation modeling, including sequential mediation and multigroup analysis. Findings: Both quantity-based and time-based scarcity significantly increase perceived usefulness and positive emotions, with quantity-based scarcity showing stronger effects. Perceived usefulness mediates the relationship between scarcity cues and the urge to buy impulsively, whereas the emotional pathway is significant only for quantity-based scarcity. The urge to buy impulsively emerges as the strongest predictor of impulse buying behavior. Gender differences appear only in the final stage of the process, where the conversion of the urge to buy impulsively into actual purchasing behavior is stronger among female consumers. Originality/Value: This study contributes to impulse-buying research by integrating the SOR framework with the TAM to explain the sequential process linking scarcity cues, cognitive and emotional evaluations, motivational activation, and purchasing behavior in e-commerce livestreaming environments. Practical/Policy implications: The findings suggest that the effectiveness of flash sales in livestream settings depends on reinforcing perceived usefulness before activating urgency cues and ensuring frictionless checkout when consumers’ purchase motivation peaks.